2013
DOI: 10.1017/s1474747212000340
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary savings, financial behavior, and pension finance literacy: evidence from Chile

Abstract: Link to this article: http://journals.cambridge.org/abstract_S1474747212000340How to cite this article: OSCAR M. LANDERRETCHE and CLAUDIA MARTÍNEZ (2013). Voluntary savings, nancial behavior, and pension nance literacy: evidence from Chile. AbstractChileans have limited knowledge of the pension system, its rules, and the consequences involved in their personal decisions within it. Using a variation in the household compositionhaving a pensioner in the household -as an instrument, we show that Chileans with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 33 publications
2
43
0
2
Order By: Relevance
“…Interestingly, there was no gender disparity in financial knowledge in the East Germany. Moreover, Landerretche and Martínez (2013) showed that Chileans people with greater knowledge about their pension system were more likely to have additional financial savings. Add to that, they indicated that improving in the pension literacy survey had positive influence on the personal tendency to save.…”
Section: Financial Literacy and Its Consequencesmentioning
confidence: 99%
“…Interestingly, there was no gender disparity in financial knowledge in the East Germany. Moreover, Landerretche and Martínez (2013) showed that Chileans people with greater knowledge about their pension system were more likely to have additional financial savings. Add to that, they indicated that improving in the pension literacy survey had positive influence on the personal tendency to save.…”
Section: Financial Literacy and Its Consequencesmentioning
confidence: 99%
“…Levels of financial literacy in emerging markets are lower 5 than in industrialized countries (Hastings and Tejada-Ashton, 2008, Klapper and Panos, 2011, Beckmann, 2013, especially in rural areas. At the same time, studies in developing countries confirm that better financial literacy is positively related to retirement planning (Klapper and Panos, 2011), to greater participation in financial markets, to greater use of formal sources of borrowing (Klapper et al, 2013), to higher voluntary savings (Landerretche and Martinez, 2013) and to better diversification (Beckmann, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…While the different empirical approaches used to measure people's fl have come in for criticism, it can be argued that the levels of fl found in the general population are substantially lower than they should be (Hogarth and Hilgerth, 2002;Miles, 2004;Christelis, Jappelli and Padula, 2005;Lusardi andMitchell, 2007a and2007b;Lusardi, Mitchell and Curto, 2010;Landerretche and Martínez, 2011;Van Rooij, Lusardi and Alessie, 2011;Stone and Neumann, 2012, among others). This has consistently been found to be the case in all the countries for which data are available, and fl levels are particularly low among the poorer segments of the population and among women.…”
Section: Is Financial Literacy An Economic Good? • Rubén Castro and Amentioning
confidence: 99%
“…Chan and Huff (2003) find that responses regarding self-reported knowledge provide supplementary data about the importance that people attribute to the information referred to in the question and about their degree of assurance in that regard. Landerretche and Martínez (2011) suggest that, in order to avoid overestimating the parameters in question, the results for these types of responses should be regarded as the upper limit for accurate results when the time comes to interpret them, with the assumption being that the actual value is lower.…”
Section: Is Financial Literacy An Economic Good? • Rubén Castro and Amentioning
confidence: 99%